2022
DOI: 10.3389/fnut.2022.1060436
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric and visual analysis in the field of ketogenic diet on cancer from 2012 to 2021

Abstract: Increasing evidence demonstrated that the ketogenic diet (KD) played a positive effect on cancer treatment. However, no systematic review and bibliometric analysis were conducted in this field. This study aimed to explore the current status, and reveal the potential trends and hotspots to provide a reference for future research. Publications were extracted from the Web of Science Core Collection. CiteSpace (5.6.R3) software and the website of bibliometrics were used for visual analysis. A total of 500 publicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Analysis metrics mainly included the annual number of publications, number of total citations, average citations per publication (CPP), country, institution, journal, keywords, authors, Hirsch index (H-index) (21), the impact factor (IF; 2021), and the category quartile. Additionally, the bibliometrics website (http://bibliometric.com/) was used to generate a visual cooperation map of the countries/regions, herein identifying the countries that cooperate most closely with each other (22,23).…”
Section: Data Collection and Bibliometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis metrics mainly included the annual number of publications, number of total citations, average citations per publication (CPP), country, institution, journal, keywords, authors, Hirsch index (H-index) (21), the impact factor (IF; 2021), and the category quartile. Additionally, the bibliometrics website (http://bibliometric.com/) was used to generate a visual cooperation map of the countries/regions, herein identifying the countries that cooperate most closely with each other (22,23).…”
Section: Data Collection and Bibliometric Analysismentioning
confidence: 99%
“…The different colors on the map represent the total number of publications, with the darker red color representing a higher number of publications. China was the most prolific country in this field, with 120 publications, followed by the United States (114), Italy (30), France (25), and Japan (23), while the United States had the highest H-index (31) (Figure 4A). When the country citations were analyzed, the United States, with 5,779 citations, had the highest total number of citations, followed by France (3,225), China (2,095), Canada (895), and the United Kingdom (895) (Figure 4B).…”
Section: Contributions Of Top 10 Productive Countries/regionsmentioning
confidence: 99%
“…As we report here, these authors observed a growing number of publications between 2019 and 2022, with a large body of research on breast cancer. In November of 2022 and February of 2023, two additional bibliometric analyses were published, focusing on the ketogenic and Mediterranean diets, respectively [10,11]. The ketogenic diet paper identified breast and glioma as cancer types commonly studied in the context of this diet, with the numbers of on hepatocellular and pancreatic cancers rapidly rising [10].…”
Section: Comparisons To Other Bibliometric Analysesmentioning
confidence: 99%
“…Within the cancer field, a PubMed search of "bibliometrics" and "neoplasms" (MeSH terms) indicates that more than 500 bibliometrics analyses have been conducted to date. Over the past ten years, these publications have focused on areas such as the gut microbiome [9], ketogenic diets [10], the Mediterranean diet [11], and specific cancers, including breast cancer [12]. There is also one bibliometric analysis of ~1500 papers related to cancer and nutrition published from 2011 to 2021, but this paper used only keywords that contained "nutrition", rather than a more detailed interrogation of specific dietary components [13].…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 , 28 ] It uses quantitative statistics to summarize the current status, trends, and hotspots of research topics, as well as the contributions of authors, journals, institutions, or countries. [ 29 ] Recently, scholars have used bibliometric analysis to examine the effects of certain dietary habits on physiology or pathology, such as ketogenic diet therapies for neurological diseases and cancer, [ 30 , 31 ] the Mediterranean diet on cancer, [ 32 ] and time-restricted eating. [ 33 ] Additionally, some scholars have conducted bibliometric analyses in certain areas related to CVDs, such as exosomes in CVD, [ 34 ] the gut microbiome and coronary heart disease and the use of acupuncture in heart disease.…”
Section: Introductionmentioning
confidence: 99%